2‐Chloroacetamidine, a novel immunomodulator, suppresses antigen‐induced mouse airway inflammation. Issue 9 (2nd June 2015) - Maezawa, Y.; Paltser, G.; Tsui, H.; Cheung, R.; Wu, P.; Nicholas, A. P.; Dosch, H.‐M.
Abstract Background Citrullination is a presently under‐recognized posttranslational protein modification catalyzed by PAD enzymes. Immune responses to citrullinated neo‐epitopes are identified in a growing number of inflammatory and autoimmune diseases. However, the involvement of hypercitrullination in the pathogenesis of bronchial asthma is still unknown. Methods As main experimental tool, we examined the effect of 2‐chloroacetamidine (2CA), a PAD enzyme inhibitor, on OVA‐immunized and airway‐challenged BALB/c mice; a commonly used model of allergic airway inflammation. We also measured the effect of 2CA on ex vivo lymphocytes and cell lines. Results In vivo, 2CA dramatically suppressed lung tissue hypercitrullination, inflammatory cell recruitment, and airway‐Th2 cytokine secretion. 2CA also suppressed systemic OVA‐specific and total IgE production dramatically, effectively preventing de novo and diminishing established disease without measurably impacting general immunocompetence. In vitro, 2CA markedly inhibited the proliferation of mouse and human T cells with cell cycle block and apoptosis during a limited, postactivation phase. Conclusions 2CA acts as narrow‐spectrum immunosuppressant that selectively targets lymphocyte populations involved in active inflammatory tissue lesions. If hypercitrullination is generated in patients with asthma, 2CA may represent a novel disease modulator for human asthmatics/allergic diseases.